Prevalence of Chronic Infection by Hepatitis C Virus in Asymptomatic Population With Risk Factors in Cartagena, Colombia - Imbeth-Acosta, Pedro; Leal-Martínez, Víctor; Ramos-Clason, Enrique; Pájaro-Galvis, Nehomar; Martínez-Ávila, María Cristina; Almanza-Hurtado, Amilkar; Rodríguez-Yanez, Tomás; Bermudez-Montero, Jorge; Vergara-Serpa, Oscar; Abuabara-Franco, Emilio; Raad-Sarabia, María; Villar-González, Erika Patricia; et al. (Frontiers in Medicine, 2022)
Introduction Infection by the hepatitis C virus (HCV) is an important cause of chronic liver disease, considered a public health problem worldwide with high morbidity and mortality due to limited access to diagnostic tests in developing countries. Only a small percentage know their infection status and receive timely treatment. It is critical to make diagnostic tests for HCV infection accessible and to provide timely treatment, which not only reduces the spread of infection but also stops the progression of HCV disease without symptoms. Objective To determine the prevalence of chronic infection by HCV in patients with risk factors by using rapid tests in Cartagena, Colombia, and describe their epidemiological characteristics. Methodology A cross-sectional descriptive observational study was carried out on asymptomatic adults with risk factors for HCV infection in the city of Cartagena between December 2017 and November 2019. A rapid immunochromatographic test was performed to detect antibodies, characterizing the population. Results In total, 1,023 patients were identified who met the inclusion criteria, 58.5% women and 41.4% men, obtaining nine positive results, confirming chronic infection with viral load for HCV, finding seven cases of genotype 1b and two genotype 1a. Conclusion In our study, a prevalence of hepatitis C infection of 0.9% was found in asymptomatic individuals with risk factors, which allows us to deduce that the active search for cases in risk groups constitutes a pillar for the identification of the disease, the initiation of antiviral therapy, and decreased morbidity and mortality.